Conceptual understandings and prevalence of sexual harassment and street harassment - Bianca Fileborn
This resource sheet provides an overview of the existing research on women's experiences of sexual harassment and street harassment. It also considers conceptual models of sexual violence that are inclusive of these experiences. Women's experiences of street harassment and sexual harassment are focused on in this paper. It is acknowledged that men can also be the victims of this behaviour. However, street harassment and sexual harassment are highly gendered occurrences. Women are overwhelmingly the victims and men the perpetrators. The language adopted throughout this sesource sheet reflects this gendered reality. Further, the conceptual model of sexual violence discussed later in this publication (the continuum model of sexual violence) applies more specifically to women's experiences of sexual violence across their life course. That is, women experience a broad range of sexual violence (ranging from the relatively "minor" to severe forms of sexual violation) at rates considerably higher than men. Further, while rates of victimisation remain relatively steady for women across their life course, rates of victimisation against men tend to decline across their life course.Key messages:Sexual violence, as a form of violence againt women needs to be conceptualised in a way that reflects women's actual experiences, ranging from relatively "minor" forms of sexual violence through to sexual assault and rape.The harm of sexual violence is not always directly correlated with the perceived seriousness of the behaviour. Individual women experience forms of sexual violence differently. The context behaviour occurs in also plays a role in mediating its harm.All forms of sexual violence are interconnected, and are underpinned by the same social and cultural attitudes.Sexual harassment and street harassment are highly prevalent and common experiences for women. They are often not talked about and not taken seriously as harm (particularly street harassment).Sexual harassment and street harassment need to be included in policy and legislation targeted at preventing or responding to sexual violence.Information on current responses and disclosure mechanisms is also provided towards the end of this resource